(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the importance of increasing the activity of women in the public administration system, the role of spiritual and moral qualities as a personal phenomenon, creating a portrait of a socially and politically active woman, and studying the socio-political activity of women in the public administration system